The Effect of Preoperative Type 2 Diabetes and Physical Fitness on Mental Health and Health-Related Quality of Life after Roux-en-Y Gastric Bypass - Cathrine L. Wimmelmann; Michael T. Lund; Merethe Hansen; Flemming Dela; Erik L. Mortensen (Journal of Obesity)
Objective. To investigate the predictive value of type 2 diabetes and lack of physical activity for mental health and health-related quality of life after Roux-en-Y gastric bypass. Method. Forty severely obese patients undergoing Roux-en-Y gastric bypass were included in the GASMITO study. Information about physiological and psychological factors was prospectively assessed at four time points, two times prior to surgery and two times after surgery. Measures included oral and intravenous glucose tolerance tests, VO2max test, Symptoms Checklist (SCL-90), Short Form Health Survey 36 (SF-36), Body Image Questionnaire, and a questionnaire assessing sociodemographic factors and medical status. Results. Mean % excess weight loss was 65% (±12) at 18-month follow-up and 50% of the participants with diabetes experienced total remission. Also, significant improvements were observed with regard to physical fitness, mental distress, health-related quality of life, and weight-related body image (p<0.05). The interaction between follow-up time and type 2 diabetes at baseline significantly predicted six of the thirteen psychological subscales (p<0.05) and, across the follow-ups, physical fitness level made modest contributions to variations in mental symptoms and HRQOL but not weight-related body image. Conclusion. The results suggest that baseline difference in mental symptoms and physical HRQOL between diabetic and nondiabetic patients declines across follow-ups and resolves around the time of surgery.